Numerical and experimental stress analysis of an internal-combustion engine valve during the closing event - Cavalieri, Federico José (2014)
This paper presents a numerical methodology to predict the stress evolution in internal combustion engine valves during the closing event. The problem is studied by a three-dimensional finite element model, showing that the seating process of the valve produces high bending stresses that are not captured by two-dimensional models. The valve stem stress response under impact was registered experimentally using strain gauges and then compared with the finite element method solutions, showing good agreement. The main contribution of this paper is the identification of the factors that generate the development of impact stresses during the closing event in a combustion engine valve and that could result in fatigue failure.